Psychological Care, Patient Education, Orthotics, Ergonomics and Prevention Strategies for Neck Pain: A Systematic Overview Update as Part of the ICON Project - Gross, A; Kaplani, F; Huang, S; Khani, J; Santaguida, L; Carlesso, L; Macdermid, J; Walton, D; Kennardy, J; Reid, DA (Bentham Open, 2013)
Objectives: To conduct an overview on psychological interventions, orthoses, patient education, ergonomics, and 1°/2° neck pain prevention for adults with acute-chronic neck pain. Search Strategy: Computerized databases and grey literature were searched (2006-2012). Selection Criteria: Systematic reviews of randomized controlled trials (RCTs) on pain, function/disability, global perceived effect, quality-of-life and patient satisfaction were retrieved. Data Collection & Analysis: Two independent authors selected articles, assessed risk of bias using AMSTAR tool and extracted data. The GRADE tool was used to evaluate the body of evidence and an external panel to provide critical review. Main Results: We retrieved 30 reviews (5-9 AMSTAR score) reporting on 75 RCTs with the following moderate GRADE evidence. For acute whiplash associated disorder (WAD), an education video in emergency rooms (1RCT, 405participants] favoured pain reduction at long-term follow-up thus helping 1 in 23 people [Standard Mean Difference: - 0.44(95%CI: -0.66 to -0.23)). Use of a soft collar (2RCTs, 1278participants) was not beneficial in the long-term. For chronic neck pain, a mind-body intervention (2RCTs, 1 meta-analysis, 191participants) improved short-term pain/function in 1 of 4 or 6 participants. In workers, 2-minutes of daily scapula-thoracic endurance training (1RCT, 127participants) over 10 weeks was beneficial in 1 of 4 participants. A number of psychosocial interventions, workplace interventions, collar use and self-management educational strategies were not beneficial. Reviewers' Conclusions: Moderate evidence exists for quantifying beneficial and non-beneficial effects of a limited number of interventions for acute WAD and chronic neck pain. Larger trials with more rigorous controls need to target promising interventions.
Keywords: Overview; Psychological; Education; Orthotics; Ergonomics; Prevention; Neck pain